IMPLEMENTASI BUSINESS INTELLIGENCE UNTUK PENILAIAN MUTU PELAYANAN DI RUMAH SAKIT UMUM DAERAH TULANG BAWANG BARAT - Nia Marsela; Bambang Hermanto (Jurnal Pepadun, 2022)
KMK number 340 about the classification of hospitals, hospitals must have the ability to serve at least general medical services, emergency services, nursing services, outpatient care, inpatient care, surgery, basic specialist medical services, medical support, pharmacy, nutrition, sterilization, medical records, administrative and management services, public health counseling, relocation of corpses, laundry, and ambulances, maintenance of hospital facilities, and waste treatment. Business Intelligence is one solution so that hospital management gets information about service quality assessments that can help make decisions. The application used to implement Business Intelligence is Google Data Studio. This study uses six indicators of hospital quality service standards (SPM), namely Bed Occupancy Rate (BOR), Turn Over Interval (TOI), Average Length of Stay (ALOS), Bed Turn Over (BTO), Net Death Rate (NDR), and Gross Death Rate (GDR). The data variables that need indicator values are time, number of patients, number of patients discharged, number of patients dying >48 hours, number of dead patients, number of days of treatment, number of lengths of stay and number of beds. The data is processed by the Extract, Transform, Load (ETL) process to form a data warehouse. The data contained in the data warehouse will be visualized on Google Data Studio.